2012
DOI: 10.4239/wjd.v3.i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Role of nuclear factor (erythroid-derived 2)-like 2 in metabolic homeostasis and insulin action: A novel opportunity for diabetes treatment?

Abstract: Redox balance is fundamentally important for physiological homeostasis. Pathological factors that disturb this dedicated balance may result in oxidative stress, leading to the development or aggravation of a variety of diseases, including diabetes mellitus, cardiovascular diseases, metabolic syndrome as well as inflammation, aging and cancer. Thus, the capacity of endogenous free radical clearance can be of patho-physiological importance; in this regard, the major reactive oxygen species defense machinery, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 104 publications
(72 reference statements)
1
21
0
1
Order By: Relevance
“…It has been reported that PA can lower blood pressure (Eriksson et al, 1997;Miller et al, 2002), increase insulin sensitivity, decrease abdominal fat (Burstein et al, 1985;Olsen et al, 2008), activate the expression of cellular antioxidant systems (Sachdev & Davies, 2008), and induce anti-inflammatory effects (Jansen et al, 2010;Yu et al, 2012). However, these data do not explain the differences between vigorous and moderate PA in reducing risk of MS. Trapp and colleagues reported that high-intensity interval training caused a significant reduction in total body fat compared with low-intensity steady state exercise in young women (Trapp et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that PA can lower blood pressure (Eriksson et al, 1997;Miller et al, 2002), increase insulin sensitivity, decrease abdominal fat (Burstein et al, 1985;Olsen et al, 2008), activate the expression of cellular antioxidant systems (Sachdev & Davies, 2008), and induce anti-inflammatory effects (Jansen et al, 2010;Yu et al, 2012). However, these data do not explain the differences between vigorous and moderate PA in reducing risk of MS. Trapp and colleagues reported that high-intensity interval training caused a significant reduction in total body fat compared with low-intensity steady state exercise in young women (Trapp et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…The relationship between Nrf2 and the insulin signaling pathway becomes important in the context of insulin resistance, which has been recently reviewed by Yu and colleagues [34]. A conundrum exists, however, in the roles that Nrf2 and insulin have in lipid synthesis.…”
Section: Regulation Of Liver Energy Metabolismmentioning
confidence: 96%
“…Recently, the antioxidant potential of polyphenols was attributed to its ability to activate Nrf-2, an important cellular defence mechanism to cope with oxidative stress. The role of Nrf-2 in protecting the vascular complications in diabetes has been emerging and is reported to regulate lipid metabolism [9]. Hence, evaluating efficacy of drug candidates like polyphenols in context with Nrf-2 functional status will shed insights upon its antioxidant potential and can offer promising avenues in therapeutic management of DM.…”
Section: Introductionmentioning
confidence: 99%